PEMAHAMAN KONSEP “WALL-LESS-NESS” DALAM PEMBELAJARAN BERBASIS ALAM DI KINDERGARTEN GREEN SCHOOL BALI - Betty Yulia Wulansari (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2019)
The purpose of this research is to understand the concept of "Wall Less-Ness" in Nature Based Learning at Green School Bali. The research is a phenomenological qualitative research to explore the phenomenon of the "Wall Less-Ness" concept in Nature Based Learning at Green School Bali. Research on Understanding the Concept of "Wall-Less-Ness" in Bali's Green School Kindergarten has the following conclusions: The aim of the concept of "Wall-Less-Ness" is to bring children closer to the natural environment. With buildings that lack walls, natural green environments make natural learning unite with the child's soul. In addition, the purpose of this concept is to provide a cultural culture that lives that emphasizes sustainable environment in children from an early age. The benefits of the Wall-Less-Ness concept are the first availability of learning resources, learning media and adequate learning places from the surrounding world. Second, saving energy. Third, children understand the importance of a sustainable environment for human survival. The Advantages of the Wall-Less-Ness Concept in Kindergarten Green School learning is facilitating the learning process in accordance with the characteristics of early childhood learning, having more value in learning programs that promote sustainability, having learning outcomes that benefit life, having challenges in learning, growing education strong character for early childhood, and growing a sense of love for the environment, being able to think about environmental sustainability going forward and having a very complete learning environment for early childhood learning in accordance with the vision of Green School. While the lack of this concept is very expensive tuition fees that can only be accessed by foreigners. As well as some behaviors in the learning process it is difficult for Indonesians to accept because many western cultures are accommodated into habits.